The vegetable alkaloids their chemical composition and their physiological effects - Pritner, Mary Bly (My University, 1899)
Introduction: Of the many organic compounds found in the vegetable world, there is a considerable number that are very complex in composition but very important because of their frequent occurrence, common usage and great medical activity. Some of these have been used for ages, either in medicine or habitually in daily fife, but use because of physiological effects and without a definite knowledge of their chemical composition and conduct. Among the most important and most complex of these are the vegetable alkaloids, which are sometimes designated chemically as the Pyridine bases. They are found in a variety of plants; and are nitrogenous organic compounds, also called bases as they are capable of neutralizing acids. They are divided into two cases – the volatile and non-volatile (1) The volatile are compounds of carbon, hydrogen and nitrogen.
Citation: Pritner, Mary Bly. The vegetable alkaloids their chemical composition and their physiological effects. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Classification; Reactions for Alkaloids; General Chemical Properties; Examples of Comon Alkaloids; Theses; Manuscripts (documents)